Collaborative internet of things (C-IOT) : for future smart connected life and business - Behmann, Fawzi; Wu, Kwok (Wiley ; IEEE, 2015)
"Provides a simplified visionary approach about the future direction of IoT, addressing its wide-scale adoption in many markets, its interception with advanced technology, the explosive growth in data, and the emergence of data analytics"--Resumé vydavatele
Keywords: internet věcí; vestavěné systémy; Internet of things; embedded systems; monografie; monographs